EFFECTIVENESS OF RESTORATIVE JUSTICE IMPLEMENTATION IN RESOLVING ORDINARY CRIMINAL CASES AT BARRU DISTRICT POLICE - Syamsul Bahri; Muhammad Natsir; Aksah Kasim; Sunardi Purwanda; Muhammad Sabir (RADJA PUBLIKA, 2026)
This study examines the effectiveness of restorative justice in the resolution of general criminal offenses at Polres Barru within the framework of criminal law enforcement in Indonesia. The research employs a normative legal research method, focusing on the analysis of statutory regulations, legal principles, and doctrinal perspectives, particularly Law Number 2 of 2002 on the Indonesian National Police, Law Number 1 of 2023 on the Criminal Code, and Regulation of the Chief of Police Number 8 of 2021 concerning the handling of criminal cases based on restorative justice. The study applies statute and social approaches to assess the consistency and effectiveness of restorative justice implementation at the investigative level. The findings indicate that restorative justice has contributed to improved legal effectiveness by promoting victim recovery, offender responsibility, and social reconciliation, while also enhancing procedural efficiency. However, its implementation faces challenges related to regulatory clarity, law enforcement discretion, and uniformity of application. This study concludes that strengthening normative guidelines and institutional capacity is essential to ensure the sustainable and equitable application of restorative justice in criminal law enforcement.